Penularan Penyakit Layu Bakteri dan Hasil Kacang Tanah Lokal dengan Penambahan Dosis Bertingkat Pupuk K - Widiastuti, Eka; Fitrahtunnisa, Fitrahtunnisa; Zulhaedar, Fitria (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2021)
Bacterial wilt R. solanacearum is one of the main diseases of peanuts that can reduce crop production. The use of local varieties and plant management can control bacterial wilt disease. Local varieties are one source of germplasm diversity for plant breeding activities. Management such as fertilization is expected to control pests and plant diseases. The aim of the study was to determine the performance of bacterial wilt disease and its effect on the yield of three local peanut varieties in West Nusa Tenggara with the addition of various doses of K fertilizer. The study was conducted at the Narmada Visitor Plot, on 17 January - 29 April 2017. The experiment used a split plot factorial design. The main plots were three varieties of local NTB peanuts, namely local peanuts North Lombok (KLU) (V1), local Bima (V2), and local Pelat (V3). Subplots are four levels of potassium (K) fertilizer dose, namely 0 kg KCl/ha (P1), 20 kg KCl/ha (P2), 40 kg KCl/ha (P3), and 60 kg KCl/ha (P4). Each treatment was repeated five block. The results showed that each local peanut varieties with doses of KCl fertilizer showed bacterial wilt resistance. The lowest transmission of bacterial wilt was in KLU local peanuts with a dose of 0 kg KCl/ha, 20 kg KCl/ha, and 40 kg KCl /ha, Bima at a dose of 40 kg KCl/ha and Pelat at a dose of 60 kg KCl/ha. The application of KCl fertilizer at a dose of 0 kg/ha to 60 kg/ha did not affect the yield and varieties of local peanuts had different weights of 100 seeds in response to the application of K fertilizer, local peanuts KLU and Pelat had the highest weights of 100 seeds at the KCl dose. 40 kg/ha while Bima at a dose of KCl 60 kg/ha.